1988
DOI: 10.1111/j.1540-8159.1988.tb05982.x
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous Pacing for Cardiac Emergencies

Abstract: Transcutaneous cardiac pacing using the Pace-Aid (Cardiac Resuscitator Corporation) was assessed in 32 emergency patients presenting with profound bradycardia or asystole who had failed to recover with advanced life support including the use of epinephrine. Pacing stimuli, pulse width 20 ms at 50, 100, or 200 mA, were delivered through two 8 cm gel-pad electrodes placed antero-posteriorly on the chest. By ECG criteria, definite electrical capture was achieved in a total of five patients and possible capture in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…Four case series (LOE 4) demonstrated that in-hospital transcutaneous pacing had slightly higher success rates for rhythm capture 401 and survival to discharge (18% to 75%) [402][403][404] compared with survival-to-discharge rates (69%) when transcutaneous pacing was given for out-ofhospital bradycardia (LOE 1). 405 A systematic review supported this survival-to-discharge rate of 15% to 70% in the prehospital setting (LOE 3).…”
Section: Consensus On Sciencementioning
confidence: 99%
“…Four case series (LOE 4) demonstrated that in-hospital transcutaneous pacing had slightly higher success rates for rhythm capture 401 and survival to discharge (18% to 75%) [402][403][404] compared with survival-to-discharge rates (69%) when transcutaneous pacing was given for out-ofhospital bradycardia (LOE 1). 405 A systematic review supported this survival-to-discharge rate of 15% to 70% in the prehospital setting (LOE 3).…”
Section: Consensus On Sciencementioning
confidence: 99%
“…The unique non-invasive method is the transcutaneous transthoracic electrical stimulation. This technique is frequently not accepted by patients because of the discomfort of the subcutaneous stimulation of the thoracic musculature as effective cardiac pacing requires high intensity pulses most of the time5.…”
mentioning
confidence: 99%
“…The different indications for transvenous versus transcutaneous temporary pacing are not well described in the literature. Transcutaneous pacing has advantages of being rapidly applied and does not require the same degree of technical expertise, equipment, or sterile insertion 4,7 . This makes it the temporary pacing mode of choice in the prehospital setting.…”
Section: Discussionmentioning
confidence: 99%